1988
DOI: 10.1677/joe.0.1170223
|View full text |Cite
|
Sign up to set email alerts
|

The role of thyroid hormones in the growth hormone response to protein restriction in the domestic fowl (Gallus domesticus)

Abstract: The possible role of thyroid hormones in the rise in plasma GH observed in protein-restricted chicks was examined. Increased sensitivity of protein-restricted chicks to secretagogue challenge (TRH or GH-releasing factor) appears to account, at least in part, for increased GH concentrations in protein-restricted chicks. Thyroid hormones administered acutely were able to suppress plasma GH concentrations in protein-restricted chicks. Further, chronic thyroid hormone supplementation to low protein diets normalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…These results support the hypothesis that serum IGF‐I plays a role in growth and in efficiency of feed utilization in beef cattle. Chickens consuming a low protein diet exhibit depressed plasma IGF‐I concentrations, which return to normal on restoration of dietary protein (Lauterio and Scanes, 1988; Rosebrough et al., 1989; Rosebrough and McMurtry, 1993). Studies showed that protein deficiency (Thissen et al., 1994; Ketelslegers et al., 1995) and methionine deficiency could depress the IGF concentration in small rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…These results support the hypothesis that serum IGF‐I plays a role in growth and in efficiency of feed utilization in beef cattle. Chickens consuming a low protein diet exhibit depressed plasma IGF‐I concentrations, which return to normal on restoration of dietary protein (Lauterio and Scanes, 1988; Rosebrough et al., 1989; Rosebrough and McMurtry, 1993). Studies showed that protein deficiency (Thissen et al., 1994; Ketelslegers et al., 1995) and methionine deficiency could depress the IGF concentration in small rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted by Scanes et al (1981) and Lauterio and Scanes (1988) have confirmed that fasting birds and those consuming diets with some nutrient restrictions (protein or energy) display reduced IGF-I mRNA expression. Rosebrough and McMurtry (1993) have also observed lower plasmatic IGF-I levels in broilers under nutrient restriction.…”
Section: Discussionmentioning
confidence: 96%
“…In females, TRH had no effect on growth parameters. Previous observations on chickens (Harvey et al, 1978;Burkę, 1983;Leung et al, 1984;Lauterio and Scanes, 1987) and ducks (Folzer-Joudaione et al, 1988) established that TRH not only stimulates the release of thyroid hormones but also is a potent stimulant of GH secretion. Remarkable differences in GH response between małe and female broilers were seen in the form of higher plasma GH concentrations in males (Harvey et al, 1977;Johnson et al, 1990).…”
Section: Discussionmentioning
confidence: 98%